2015
DOI: 10.1016/j.jdent.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Transdentinal cytotoxicity of glutaraldehyde on odontoblast-like cells

Abstract: Objectives This study investigated the transdentinal cytotoxicity of glutahaldehyde-containing solutions/materials on odontoblast-like cells. Methods Dentin discs were adapted to artificial pulp chambers. MDPC-23 cells were seeded on the pulpal side of the discs and the occlusal surface was treated with the following solutions: water, 2%glutaraldehyde (GA), 5%GA, 10%GA, Gluma Comfort Bond+Desensitizer (GCB+De) or Gluma Desensitizer (GDe). Cell viability and morphology were assessed by the Alamar Blue assay a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 41 publications
(56 reference statements)
1
22
0
4
Order By: Relevance
“…Despite reports showing effective MMP inhibition with HEMA (42,43), the frequently reported fall in lTBS of HEMA-containing adhesives (44,45) may indicate that the MMPinhibitory effects of HEMA are lost when it is co-polymerized with other adhesive monomers (43). Moreover, recent findings by our group have also indicated that HEMA may be responsible for the cytotoxicity associated with Gluma dentin desensitizer (46). Gluma, traditionally marketed for desensitizing purposes, requires HEMA for reasons such as tubular blockage and dentin-permeability reduction, which can only occur when both active components are present.…”
Section: Discussionmentioning
confidence: 93%
“…Despite reports showing effective MMP inhibition with HEMA (42,43), the frequently reported fall in lTBS of HEMA-containing adhesives (44,45) may indicate that the MMPinhibitory effects of HEMA are lost when it is co-polymerized with other adhesive monomers (43). Moreover, recent findings by our group have also indicated that HEMA may be responsible for the cytotoxicity associated with Gluma dentin desensitizer (46). Gluma, traditionally marketed for desensitizing purposes, requires HEMA for reasons such as tubular blockage and dentin-permeability reduction, which can only occur when both active components are present.…”
Section: Discussionmentioning
confidence: 93%
“…Then, the occlusal surface of each disc was ground for 10 s with 600-grit abrasive papers (Carborundum Abrasives, Recife, PE, Brazil) to obtain a homogeneous smear layer (12). The artificial pulp chamber (APC; Fig.…”
Section: Artificial Pulp Chamber (Apc)mentioning
confidence: 99%
“…In total, 3x10 4 cells in a 20-mL volume were seeded onto the pulpal side of dentin, and the sets were maintained in an incubator with 5% CO 2 at 37 °C for 30 min to allow initial cell adhesion. Then, 1 mL of complete DMEM was added to the APC/disc sets and incubated for an additional 48-hour period, allowing the pulp cells to spread and proliferate on dentin substrate (12).…”
Section: Properties Of Universal Adhesive Systemsmentioning
confidence: 99%
“…Chemical crosslinkers have been employed to improve the mechanical properties and the resistance to enzymatic hydrolysis of the dentin collagen. However, some effective crosslinking agents, such as glutaraldehyde or grape seed extract, have shown only limited effectiveness in their actual in vivo applications, because of the formation of highly cytotoxic byproducts by the reaction or the possible discoloration of the collagen fibers 5,6) . Physical crosslinking is one alternative method that can improve the biomechanical rigidity of the collagen fibrils, as it leaves no residues following treatment and the rigidity remains stable over time 7,8) .…”
Section: Introductionmentioning
confidence: 99%